2021
DOI: 10.1186/s12951-021-00796-6
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles reduce inflammation in cerebral microvessels of mice with sepsis

Abstract: Background Sepsis is an emergency medical condition that can lead to death and it is defined as a life-threatening organ dysfunction caused by immune dysregulation in response to an infection. It is considered the main killer in intensive care units. Sepsis associated-encephalopathy (SAE) is mostly caused by a sepsis-induced systemic inflammatory response. Studies report SAE in 14–63% of septic patients. Main SAE symptoms are not specific and usually include acute impairment of consciousness, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 84 publications
0
21
0
1
Order By: Relevance
“…According to current research, neuroinflammation and oxidative stress are key factors in the development of SAE, and inhibiting inflammatory reactions has a significant impact on SAE therapy. (Yeh et al, 2015;Kikuchi et al, 2019;Ismail Hassan et al, 2020;Wang et al, 2020;Di Bella et al, 2021). Therefore, elucidating mechanisms of the inflammation and oxidative stress that are closely related to the occurrence of SAE will be important for the development of drugs to treat SAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to current research, neuroinflammation and oxidative stress are key factors in the development of SAE, and inhibiting inflammatory reactions has a significant impact on SAE therapy. (Yeh et al, 2015;Kikuchi et al, 2019;Ismail Hassan et al, 2020;Wang et al, 2020;Di Bella et al, 2021). Therefore, elucidating mechanisms of the inflammation and oxidative stress that are closely related to the occurrence of SAE will be important for the development of drugs to treat SAE.…”
Section: Discussionmentioning
confidence: 99%
“…Kikuchi et al showed that inhibition of poldip2 could attenuate BBB disruption caused by sepsis by regulating the nuclear translocation process of NF-κB as well as Cox-2 expression, preventing the occurrence and development of SAE ( Kikuchi et al, 2019 ) ( Figure 2 ). Di Bella et al found that citrate-covered gold nanoparticles (Cit-AuNP) could prevent the process of NF-κB translocation to the nucleus by decreasing the phosphorylation of inhibitor of kappa B alpha (IκBα), which was followed by decreased expression of pro-inflammatory factor ICAM-1 on leukocytes and reduced adhesion of leukocyte to the endothelium of intracerebral blood vessels, ultimately alleviating the inflammatory response in the brain by BBB protection and reducing the occurrence of SAE during sepsis ( Di Bella et al, 2021 ) ( Figure 2 ). Wang et al found that by inhibiting soluble epoxide hydrolase (sEH) using TPPU(N-[1-(1-oxopropyl)-4-piperidinyl]-N’-[4-(trifluoromethoxy)phenyl)-urea), which is required for the activity of epoxyeicosatrienoic acids (EETs), a substance involved in maintaining the intact structure of cerebral blood vessels, the barrier function of BBB was improved, followed by an alleviation of long-term encephalopathy in CLP model mice ( Iliff et al, 2010 ; Wang et al, 2020 ) ( Figure 2 ).…”
Section: Bbb and Saementioning
confidence: 99%
“…However, the bioactive potential of fisetin in sepsis and SAE has not been completely elaborated. Sepsis is a common but lethal cause for multiple organ dysfunction, and SAE is the pathological change when septic damages spread to the brain, characterized by diffused brain dysfunction 22 . Based on recent studies, many brain areas, including the cortex, thalamus, hippocampus, striatum, basal ganglia, and corpus callosum could be affected by CLP 23–25 .…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is a common but lethal cause for multiple organ dysfunction, and SAE is the pathological change when septic damages spread to the brain, characterized by diffused brain dysfunction. 22 Based on recent studies, many brain areas, including the cortex, thalamus, hippocampus, striatum, basal ganglia, and corpus callosum could be affected by CLP. 23 , 24 , 25 Of note, the hippocampus region has a close association with cognitive impairment, 26 so the hippocampus tissue was selected for our research.…”
Section: Discussionmentioning
confidence: 99%
“…The serum gold concentration was 99.5 ± 18 ng/mL after three-day oral administration [ 55 ]. Moreover, 20-nm citrate-covered gold nanoparticles (cit-AuNP) reduced the adhesion of white blood cells and platelets to cerebral blood vessels, prevented BBB failure, and reduced the concentration of TNFF-α in the brain, as well as the expression of ICAM-1 in circulating polymorphonuclear (PMN) leukocytes and cerebral blood vessels in septic mice [ 56 ]. The combination of nanogold and antibiotics may be a potential drug candidate for the treatment of sepsis, to avoid sepsis-related encephalopathy.…”
Section: Cardiac and Vascular Injurymentioning
confidence: 99%